Unmaking the Japanese Miracle : Macroeconomic Politics, 1985-2000 - Grimes, William M. (Ithaca, NY : Cornell University Press, 2018)
In recent years, Japan's economy has gone from model of success to object lesson in failure. William W. Grimes offers a richly detailed insider's view of the key macroeconomic policies and events in contemporary Japan, as well as a close examination of the causes and effects of these upheavals. A new preface sets the book's findings in the context of the continuing intensification of Japan's financial woes.It is difficult to believe that the "Bubble Economy" of the late 1980s and the failed attempts at economic stimulation in the following decade both arose from the same policies. In Unmaking the Japanese Miracle, Grimes shows that this is precisely what happened. Focusing less on what went wrong than on why it went wrong, Grimes finds that mistaken macroeconomic policies--loose money in the late 1980s, excessively tight money until 1992, and only grudging use of expansionary fiscal policy until 1998--largely caused Japan's economic problems. Based on scores of interviews with Japanese policymakers, his is the first political explanation of why these catastrophic policies were carried out by the Ministry of Finance, the Bank of Japan, and the Diet. Various economic shocks were met, Grimes says, with a consistent and often inappropriate pattern of responses. This pattern has fundamentally altered because of changes within the three policymaking institutions since 1998.
Frontmatter -- Contents -- Preface to the Cornell Paperbacks Edition Over -- Acknowledgments -- Introduction: A Miracle Unmade -- A Note on Japanese Names and Terms -- Abbreviations -- 1. Organizational Conflict -- 2. Institutional Actors -- 3. Macroeconomic Policy Tools -- 4. Plaza-Louvre Period, 1985-87 -- 5. Inflating and Bursting the Bubble, 1988-92 -- 6. Dealing with Stagnation, 1993-97 -- 7. Structural Changes, 1997-2000 -- 8. Conclusions: Fighting the Last War? -- References -- Index
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mrz 2019).
Includes bibliographical references (p. 230-245) and index.
JSTOR
Keywords: Structural adjustment (Economic policy) -- Japan; Japan -- Economic policy -- 1989-; Ajustement structurel (Économie) -- Japon; Japon -- Politique économique -- 1989-; POLITICAL SCIENCE / Political Economy; Economic policy; Structural adjustment (Economic policy); Japan; Economische politiek; Since 1989